2022
DOI: 10.1097/der.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Contact Dermatitis of the Scalp Associated With Scalp Applied Products: A Systematic Review of Topical Allergens

Abstract: Hair products are commonly used to maintain hair health or cosmesis. Products applied to the scalp and hair contain multiple active and inactive ingredients that can potentially cause irritant and/or allergic contact dermatitis. The objectives of this study were to identify and to discuss the most common allergens in scalp and hair applied products causing scalp allergic contact dermatitis (ACD). A PubMed search identified 99 studies, with 3185 patients and 31 categories of scalp products. Hair products report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 112 publications
0
6
0
1
Order By: Relevance
“…Focusing on scalp ACD, based on a search of studies covering the period from 1948 to 2021, Pham et al 1 reported that the most common patch test‐positive allergens were p ‐phenylenediamine (PPD) (23%), nickel (15%), fragrance mix (13%), balsam of Peru (10%), CAPB/DMAPA (7%) and methylchloroisothiazolinone (MCI)/methylisothiazolinone (MI) (6%). Based on NACDG patch test results obtained between 2001 and 2016, 16 they showed that the causal allergens of scalp ACD were PPD (35.8%), MI (9.7%), MCI/MI (8.7%), CAPB (5.9%), AA (4.8%) and DMAPA (4.3%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on scalp ACD, based on a search of studies covering the period from 1948 to 2021, Pham et al 1 reported that the most common patch test‐positive allergens were p ‐phenylenediamine (PPD) (23%), nickel (15%), fragrance mix (13%), balsam of Peru (10%), CAPB/DMAPA (7%) and methylchloroisothiazolinone (MCI)/methylisothiazolinone (MI) (6%). Based on NACDG patch test results obtained between 2001 and 2016, 16 they showed that the causal allergens of scalp ACD were PPD (35.8%), MI (9.7%), MCI/MI (8.7%), CAPB (5.9%), AA (4.8%) and DMAPA (4.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, patients with scalp dermatitis often end up applying several kinds of topical steroids with minimal relief. Pham et al 1 recently summarized 99 studies of 3185 patients with allergic contact dermatitis (ACD) of the scalp (identified through a PubMed search) and reported that hair dyes (41%), shampoos (28%) and conditioners (22%) were the most common causative topical products. The most common ingredients in shampoos that caused scalp ACD included surfactants, such as cocamidopropyl betaine (CAPB) and cocobetaine.…”
Section: Introductionmentioning
confidence: 99%
“…Lotions, including propylene glycol 20 as a vehicle and minoxidil, commonly harbor these key allergens. Clinical manifestations require differential diagnosis with seborrheic dermatitis or psoriasis, including erythema, pruritus, scaling, and dryness of the scalp 1,3 .…”
Section: Allergensmentioning
confidence: 99%
“…The use of topical steroids and oral antihistamines usually resolves dermatitis rapidly, with systemic steroids required only in severe cases. Patch test confirms the diagnosis and facilitates allergen avoidance and the selection of alternative products based on available series combined with the ingredients of the suspected elicitors [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Die Analyse von Epikutantestdaten des IVDK bei Kundinnen, die Haarkosmetika angewandt und Hautsymptome entwickelt hatten, ergab etwa eine Positivitätsrate von 27,0 % für p-Phenylendiamin [8]. Ein aktuelles Review bestätigt die kausale Bedeutung der kosmetischen Haarfarben für Dermatitiden der Kopfhaut [9].…”
Section: Spektrum Und Häufigkeit Unerwünschter Wirkungen Von Kosmetikaunclassified